Effect of xanthan and guar gums on the formation and stability of soy soluble polysaccharide oil-in-water emulsions. (April 2015) - Chivero, Peter; Gohtani, Shoichi; Yoshii, Hidefumi; Nakamura, Akihiro
Abstract: The incorporation of relevant amounts of non-adsorbing hydrocolloids to oil-in-water (O/W) emulsions is a suitable alternative to reduce creaming. The effect of incorporating xanthan gum (XG) or guar gum (GG) in soy soluble polysaccharide (SSPS) stabilized oil-in-water (O/W) emulsions was studied. The emulsions contained 6 wt.% of SSPS, 20 wt.% Perilla seed oil (PSO), an omega-3 vegetable oil, and variable amounts of XG or GG ranging from 0.03 to 0.3 wt.%. The presence of minute amounts of XG or GG in fresh emulsions significantly decreased the emulsion droplet size (EDS) although such low concentrations did not provide enough continuous phase viscosity to arrest creaming. Emulsion microstructure indicated the presence of flocculation even at high concentrations of XG or GG caused by a depletion mechanism. All emulsions with XG or GG exhibited pseudoplastic behavior while the control emulsions showed an almost Newtonian behavior. Emulsion droplet polydispersion generally decreased with increase in the continuous phase viscosity indicating the importance of continuous phase viscosity in the dissipation of shear energy throughout the emulsion during homogenization. The characteristics of the emulsions were closely related to the rheological changes of the continuous phase. Highlights: SSPS stabilized O/W emulsions were formulated. Incorporation of xanthan or guar gums increased stability. Depletion flocculation occurred consequently leading to creaming. Incorporation of gums produced pseudoplastic emulsions. Xanthan gum has better suspension ability than guar gum.